Development of Employability Skills through Work-Based Learning - Thapa, Harish Singh (Journal of Technical and Vocational Education and Training, 2024)
Employability is the ability to participate in the workforce. It comprises a variety of elements that are required to obtain employment, while the skills needed to get employment are employability skills. These skills are essential for upgrading knowledge, skills, ability, and entrepreneurial enthusiasm of a learner. Work-based Learning (WBL) is an education strategy that increases participation in Technical and Vocational Education and Training (TVET) because there is support to enhance employability and upgrading skills for a competitive market. The aim of this article is to systematically review published research and explore the employability skills enhanced by WBL through the school-production unit. The finding of the review shows WBL in the school production unit of TVET institute is a positive indicator of employability, and they develop valuable competencies and employability skills. The review further shows that students enhance subject-specific technical skills, generic skills, or soft skills like communication skills, teamwork, problem-solving skills, critical thinking, leadership skills, entrepreneurial skills, and management skills. Likewise, they enhance personal skills like self-confidence, a positive attitude, and ethics. The article concludes that students gained their technical, generic, and personal employability skills from WBL through the school production unit in TVET institutions.